Pengaruh Struktur Modal, Tingkat Suku Bunga Dan Price Earning Ratio Terhadap Return Saham - Nurqomaria Nurqomaria; A. Agus Priyono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe purpose of this study is to determine the effect of simultaneous and partial capital structure, interest rate and price earning ratio on the stock return in property and real estate companies listed on the Indonesia Stock Exchange in the period 2016-2018, using a purposive sampling method with data from 61 samples to 45 because there are 16 samples that do not meet the sample selection criteria. This type of research is explanatory research. The method used in this study is a multiple linear regression method. The results of this study found that simultaneous capital structure (DER), interest rates (BI Rate) and price earning ratio have a significant effect on stock return. And that partial capital structure (DER) and price earning ratio have not significant effect on stock return, interest rates (BI Rate) have a significant effect on stock return. Keywords: Capital Structure, Interest Rate, Price Earning Ratio, Stock Return.